Rhythm: Perception and Production - Desain, Peter; Windsor, Luke (Lisse Swets & Zeitlinger, 2000)
This primer, designed for those interested in the perception of rhythm, provides readers with both an overview of recent research in the introductions to each section, and a broad selection of chapters dealing with more detailed studies. It consists of contributions by some of the most respected investigators in the fields of motor behaviour, timing control, music cognition and psychology and arose out of the 7th Workshop on Rhythm Perception and Production, held in Wassenaar in 1998.;The book begins with a discussion of more generic studies of timing and synchronisation, focusing on the two main methods of modelling timing behaviour (the modern complex dynamics approach and the older methods of analysis of covariance) and some progress is made towards an integration of these two historically conflicting approaches. It then moves on to consider rhythm perception and production in a wide variety of contexts, with a prticular focus on music and language. The individual contributions range from attempts to model the processes involved in tracking or synchronising to an external pulse to detailed studies of the ways in which the rhythmic complexities of real musical and linguistic behaviour (such as polyrhythmic drumming) are executed and perceived.